Understanding carbon footprint: An evaluation criterion for achieving sustainable development - Fang Yu; Qian Yuan; Xuerou Sheng; Mengyue Liu; Leping Chen; Xueliang Yuan; Dantong Zhang; Shuqi Dai; Zhinan Hou; Qingsong Wang; Qiao Ma (Chinese Journal of Population, Resources and Environment)
Excessive greenhouse gas emissions lead to global warming, which poses a critical challenge for human society. Worldwide consensus that carbon emissions must be reduced to achieve sustainable development has raised research interest on the topic of carbon footprint, an assessment standard for measuring greenhouse gas emissions. To shed light on this important topic, we introduce carbon footprint-related international standards and domestic policies, and conduct quantitative and qualitative analyses to provide a comprehensive overview of the current carbon footprint literature. Specifically, through a bibliometric analysis of 13 203 carbon footprint publications circulated over the past decade, we quantify the publication volume, influence, and collaboration networks of countries/regions, institutions, and journals. The results show that publications on carbon footprint have been increasing since 2013, and more so after 2017. Regarding domain influence, China and its academic institutions show a strong influence. In addition, a cluster analysis of the keywords of all publications shows seven categories, encompassing carbon footprint accounting methods and research priorities. Furthermore, a qualitative analysis of the research methods and subjects related to carbon footprint reveals the need to increase communication and collaboration among different disciplines and countries/regions to strengthen the construction of carbon footprint systems. Accordingly, this study identifies popular topics and development trends in the carbon footprint literature to provide research direction for promoting green and low-carbon transformation of the social economy to achieve sustainable development.